2009
DOI: 10.3233/jvr-2009-0448
|View full text |Cite
|
Sign up to set email alerts
|

The national costs of supported employment to Vocational Rehabilitation: 2002 to 2006

Abstract: This study investigated the costs accrued by all supported employees (i.e., 192,756) funded by Vocational Rehabilitation from 2002 to 2006 throughout the entire United States and its territories. Costs were examined in relation to the number of hours supported employees worked, and total wages that they earned, per week. The impact of disability, presence of secondary disabilities, the supported employee's level of education and employment history were also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For example, unlike previous studies that assumed that all employers of supported employees would claim TJTCs, this study estimated that only 75% of the employers would generate this cost to taxpayers. Given that recent research has suggested relatively few employers receive these tax credits (Cimera, 2009), the percentage used here is relatively conservative. Specifically, had this study estimated that only half of the employers received tax credits, the final benefit-cost ratio for all supported employees would have been 1.61 rather than 1.46 as reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, unlike previous studies that assumed that all employers of supported employees would claim TJTCs, this study estimated that only 75% of the employers would generate this cost to taxpayers. Given that recent research has suggested relatively few employers receive these tax credits (Cimera, 2009), the percentage used here is relatively conservative. Specifically, had this study estimated that only half of the employers received tax credits, the final benefit-cost ratio for all supported employees would have been 1.61 rather than 1.46 as reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because economic outcomes, such as wages earned and subsidies received, vary considerably from supported employee to supported employee (Cimera, 2009;Kregel et al, 1989;Lam, 1986), large sample sizes are required in order for cost-efficiency research to be representative of the entire population being served by supported employment. Unfortunately, many of the costefficiency studies currently available in the literature have sample sizes of less than 500 participants (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To put these findings in a familiar context, in FY 2006 Vocational Rehabilitation (VR) spent $189,245,184 on supported employees nationally (Cimera, 2009b). According to Braddock, Hemp, and Rizzolo (2008), $708,872,399 additional non-VR dollars were spent on supported employment in the same year for a total fiscal outlay of nearly $900 million.…”
Section: Discussionmentioning
confidence: 99%
“…Stated another way, Cimera (2009b) found that VR spent an average of $4,688 per supported employee in FY 2006. If all supported employees had the same returns on investment averaged by the community-based cohort presented in this study, an extra 139,931 individuals with disabilities could have been served by VR with only the resulting monetary benefits to taxpayers.…”
Section: Discussionmentioning
confidence: 99%